Новые виды орехотворок рода Phanacis Foerster (Hymenoptera, Cynipoidea) из стеблей Centaurea - Дьякончук, Л.А. (Вестник зоологии, 1980)
Four new species of gall-forming wasps of the Phanacis genus are described: Ph. varians sp. n., Ph. crassinervis sp. n., Ph. parvulus sp. n., Ph. lucidulus sp. n. They develop in stem of various Centaurea. Identification key of species belonging to the Phanacis genus of the USSR fauna is presented